1981
DOI: 10.1029/ja086ia05p03357
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations on ion acoustic double layers

Abstract: A comprehensive numerical study of ion acoustic double layers has been performeu for both periodic as well as for nonperiodic systems by means of one-dimensional particle

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(43 citation statements)
references
References 26 publications
2
41
0
Order By: Relevance
“…The influx of current into the magnetic field flux tubes must be balanced by that across the magnetic field. If there is to be a net current out of the simulation, then, to be totally self-consistent, one needs to treat it as part of a circuit as did Sato and Okuda [37]. For discussion see Reference [43].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The influx of current into the magnetic field flux tubes must be balanced by that across the magnetic field. If there is to be a net current out of the simulation, then, to be totally self-consistent, one needs to treat it as part of a circuit as did Sato and Okuda [37]. For discussion see Reference [43].…”
Section: Resultsmentioning
confidence: 99%
“…In their support simulations by Wagner showed double-layers to develop in the presence of just a current sheet [51]. Sato and Okuda [36,37] performed a series of simulations using even "more realistic" conditions. Their model ( Fig.…”
Section: )mentioning
confidence: 99%
“…The basic mechanism which produces weak ion-acoustic double layers is a current interruption caused by a negative potential spike. This fact was primarily recognized in onedimensional periodic simulations (Sato and Okuda, 1981 ;Kindel et al, 1981 ;Hasegawa and Sato, 1982;Nishihara et al, 1982;Chanteur et al, 1983) and has been recently confirmed in the two-dimensional case with a strong magnetic field and under various boundary conditions (Barnes et al, 1985). The theoretical explanation given to the appearance and the growth of a double layer (Hasegawa and Sato, 1982;Nishihara et al, 1982;Chanteur et al, 1983;Chanteur, 1984) turns out to be more or less independent of the linear instability.…”
Section: Introductionmentioning
confidence: 97%
“…It is not known whether this effect is due to the under-resolution of the aperture itself (and its fields) or of the ion acoustic mode wavelength near the aperture. Ion acoustic double layers have been reported [17,20] to form a dip in φ and n p on the low potential side, and such dips are regularly revealed in MNX simulations and experiments. Some additional discussion on the possible role of IAWs is provided in Sec.…”
Section: Steady-state Plasma and Double Layer Profilesmentioning
confidence: 99%